2015
DOI: 10.1186/s12966-015-0178-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between park features and adolescent park use for physical activity

Abstract: BackgroundEighty per cent of adolescents globally do insufficient physical activity. Parks are a popular place for adolescents to be active. However, little is known about which park features are associated with higher levels of park use by adolescents.ObjectivesThis study aimed to examine which environmental park features, and combination of features, were correlated with higher levels of park use for physical activity among adolescents. By examining park features in parks used by adolescents for physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 36 publications
(55 reference statements)
7
59
0
1
Order By: Relevance
“…It could be observed that parks/woods were OPSs that obtained more than four physical activity facilities (44.4%). Possibly these spaces may be the greatest potentiates of engagement in physical activities, due to their larger area in square meters, and to the greater amount of sport-recreational events by the greater number of physical activity facilities present in these spaces [19][20][21] , as observed in other studies 24,25 . Evidence shows that the frequency of use of a OPS can be justified by the types of physical activities offered 20,21 .…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…It could be observed that parks/woods were OPSs that obtained more than four physical activity facilities (44.4%). Possibly these spaces may be the greatest potentiates of engagement in physical activities, due to their larger area in square meters, and to the greater amount of sport-recreational events by the greater number of physical activity facilities present in these spaces [19][20][21] , as observed in other studies 24,25 . Evidence shows that the frequency of use of a OPS can be justified by the types of physical activities offered 20,21 .…”
Section: Discussionmentioning
confidence: 66%
“…The presence of trash cans (45.8%), benches (55.1%) and picnic tables (29.0%) with good quality in the spaces evaluated also serve to support moments of rest, socialization and contemplation 18 . Evidence shows that each new comfort attribute perceived in parks increases by three times the probability of being highly used 19 . Thus, the maintenance, aesthetics and good quality of OPS may explain, in part, why some places are more frequented than others 11,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several ways to explain park quality while most previous studies defined it as the presence of single or limited park features or characters. Some research considered park quality to the cleanliness of the park (Kaczynski, Stanis, & Besenyi, 2012) while some research considered it to the active aesthetic features in the parks (Vaughan et al, 2013) or the greenness (tree number and tree canopy area) (Edwards, Hooper, Knuiman, Foster, & Giles-Corti, 2015 (Aytur et al, 2015) was often difficult to be consistent with park quality, because higher park quality came to higher use of the park (Aytur et al, 2015;Coen & Ross, 2006;Mowen, 2010; National Recreation and Park Association, 2013), which would lead to a higher rate of crime or danger in the park.…”
Section: Park Qualitymentioning
confidence: 99%